Designing a Multipurpose Bodybuilding Club in District 3 of Tehran - Tabrizi, Sina Kamali; Farmani, Shahnaz (Journal of History Culture and Art Research, 2017)
While the sport plays an important role in the society and has a long history among the modern societies, in Iran few studies are conducted on designing and constructing sports clubs which consequently makes serious problems for the society because of the lack of principled and scientific infrastructures. Therefore, this study aims to design a multipurpose sports club in district 3 of Tehran. The method of this research is descriptive-analytical and in terms of the goal, it is practical. In addition, two clubs in district 3 of Tehran have been field visit and were analyzed by simulation. The results of the research considering climate, geographical position, site analysis, the type of sports activity, and the application of complex in urban and conceptual scale are in line with the designed results including facade, floor plans, sections, and internal and external three-dimensional designs.